Microbiological Safety Assessment of Fermented Cassava Flour “Lafun” Available in Ogun and Oyo States of Nigeria - A. O. Adebayo-Oyetoro; O. B. Oyewole; A. O. Obadina; M. A. Omemu (International Journal of Food Science)
The microorganisms involved in the fermentation and spoilage of fermented cassava flour were investigated. The water samples used at the different processing sites were also investigated to determine their safety status. There was predominance of Staphylococcus aureus, Aspergillus spp., and Escherichia coli in all samples. Coliforms were observed to be present in all of the processing water. In the fermented cassava flour, the total bacterial count ranged between 4.9×106 cfu/mL from Eleso, Bakatari, and Oja Odan processing sites and 8.10×106 cfu/mL in Eruku processing site. The majority of the microorganisms involved in the spoilage of “lafun” were found to be Aspergillus niger which ranged between 4.6×105 cfu/mL in Eleso and 8.1×105 cfu/mL in Kila. The control sample prepared in the laboratory had a low microbial load compared to samples collected from various sites and markets.